The Judge's Consideration on Interreligious Marriages in Indonesia Islamic Legal Perspective (Study Ruling Number: 508/Pdt.P/2022/Pn.Jkt Sel) - Syaifulloh Al Fariz Hakim; Arief Budiono (Proceeding International Conference Restructuring and Transforming Law, 2023)
The approach methods used is Normative Juridical. The type of secondary data is in the form of the South Jakarta District Court Decision. This research is used to find out the review of interfaith marriage according to Law No. 1 of 1974 concerning Marriage and to find out the reasons for interfaith marriage decisions based on the Council's decision. Judge Number 508/Pdt.P/2022/Pn.Jkt Sel. The South Jakarta District Court granted the request for a religious marriage. The judge assumed that there had been a legal vacuum. Because the law does not yet clearly and concretely regulate interfaith marriages. Whereas in accordance with the facts, the Petitioners have legally entered into interfaith marriages using Christian church procedures and are valid based on Christian religious law. Based on the Compilation of Islamic Law that everyone who wants to get married must adhere to the same religion. If there is a marriage of different religions, the marriage is considered invalid. Therefore, the Indonesian Ulema Council in 1980 issued a fatwa forbidding the marriage of Muslim men to non‐ Muslim women, even though members of the Illat group are people of the book, now they are classified as polytheists and infidels.